Some (Social) Aspects of Education in Transition Serbia - Šuvaković, Uroš V. (Sociološki pregled, 2019)
The paper examines the changes that education in Serbia - especially high education - has undergone during the transition period, 1989–2019. Based on the performed analysis, the author proposes to periodize changes in education and educational policy in transition Serbia. During this three-decade-long transition period, there is a clear distinction between pre-Bologna and Bologna phases in higher education. It is pointed out that the ideological basis of transitional education reform in Serbia, and especially its “Bologna phase”, is neo-liberal, globalist and anti-Enlightenment. The purpose of education has changed, so that educational institutions have become “enterprises”, which, instead of having a role of spreading enlightenment and shaping personalities with broad education, have the function of making a profit on education and, at the same time, educating young people for occupations that should contribute to GDP growth as the main criterion for the merchantability of workforce qualifications. It is clear that the results of the whole process were: the inflation of the highly educated, emigration of the best experts, the retainment of mediocre and weak experts, the lack of workers of all kinds, the promotion of technical “knowledge”, various forms of “systemic educational corruption” and neglect of the social sciences and humanities. This, of course, should also be observed through the prism of “global division of labor”: peripheral or semi-peripheral countries “export” their best experts to the center countries, like they do with other raw materials, thus financing the prosperity of the rich, while at the same time remaining in stagnant or even regressive position.